2017
DOI: 10.1111/jan.13283
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of shift work on the psychological functioning and resilience of nurses? An integrative review

Abstract: More studies are required which directly compare the psychological outcomes and resilience of nurse shift workers with non-shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 94 publications
4
58
0
2
Order By: Relevance
“…This suggests that as employees report a more negative experience of the impact of shift work on their lives (higher scores on PESW), they also experience a more negative effect in terms of self-reported psychological well-being. This reasoning is in accordance with literature indicating that the negative impact of shift work on emotional well-being is influenced by other factors, such as nurses' private lives (which impacts their experience of shift work; Peters et al;, Tahghighi et al, 2017. Moreover, the PESW construct The results further revealed that the emotional labour facet of surface acting was negatively related to psychological wellbeing at work.…”
Section: Discussion and Recommendationssupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that as employees report a more negative experience of the impact of shift work on their lives (higher scores on PESW), they also experience a more negative effect in terms of self-reported psychological well-being. This reasoning is in accordance with literature indicating that the negative impact of shift work on emotional well-being is influenced by other factors, such as nurses' private lives (which impacts their experience of shift work; Peters et al;, Tahghighi et al, 2017. Moreover, the PESW construct The results further revealed that the emotional labour facet of surface acting was negatively related to psychological wellbeing at work.…”
Section: Discussion and Recommendationssupporting
confidence: 89%
“…This suggests that if managed well, the negative implications of shift work in healthcare can be reduced. In the most recent and comprehensive review of the impact of shift work on the psychological functioning of nursing staff, Tahghighi et al (2017) concluded that no definitive evidence was found for the association between shift work and impaired psychological functioning. The authors note that overall, the findings suggest that the aforementioned association is dependent on various individual and contextual factors (Tahghighi et al, 2017).…”
Section: The Effect Of Emotional Labour and Shift Work On Pwbwmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nurses’ dissatisfaction with their working conditions, including shift work, is associated with their intention to leave the profession, which is a factor in workforce shortages, particularly with respect to the loss of experienced nurses (Nei, Anderson Snyder, & Litwiller, ; Rossi et al, ). These concerns about nursing shortages and the known influence of shift work on the workforce (Tahghighi et al, ; Tuckett, Hegney, Parker, Eley, & Dickie, ) highlight the need for studies to investigate the impact of working shifts on nurse psychological functioning. These phenomena are of interest to nurse leaders and policy makers, as both patient safety and the quality of nursing care patients receive are affected by absenteeism and staff turnover (International Council of Nurses, ).…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Tahghighi, Rees, Brown, Breen, and Hegney () did not find that shift work compared to non‐shift work impairs psychological functioning in nurses. However, one single day off was not adequate for full recovery after four successive night shifts, particularly in terms of maintaining wakefulness, perceptual motor ability and information processing (Chang, Wu, Chen, & Hsu, ).…”
Section: Discussionmentioning
confidence: 95%